PENGARUH KEPEMILIKAN SAHAM MANAJERIAL DAN INSTITUSIONAL TERHADAP NILAI PERUSAHAAN (STUDI PERUSAHAAN NON KEUANGAN DI BURSA EFEK INDONESIA) - TAMALAGI, LIDYA AVINDA (JURNAL ILMU MANAJEMEN UNIVERSITAS TADULAKO, 2017)
This study aims to study Managerial and Institutional Ownership of Value of Non-Financial Companies listed on the Stock Exchange. The independent variables consist of Managerial Share Ownership (X1) and Institutional Share (X2), as well as several control variables namely Debt, Size and Age. Dependent variable is Company Value (Y), using Tobins'Q ratio. The research sample is 110 companies with purposive sampling sampling technique. Multiple regression data analysis process. The results showed that share ownership positively and insignificantly to the control variables. The result of managerial-related imposition on a significant corporate value of 0.368%. and Institutional Share Ownership has a positive and insignificant relationship to the company with the controls, variables and companies used as control variables. The test results showed that the significant value of 0.378.